Ocean Acidification Alters the Photosynthetic Responses of a Coccolithophorid to Fluctuating Ultraviolet and Visible Radiation - Jin, Peng; Gao, Kunshan; Villafañe, Virginia Estela; Campbell, Douglas A.; Helbling, Eduardo Walter (Plant Physiology)
Mixing of seawater subjects phytoplankton to fluctuations in photosynthetically active radiation (400–700 nm) and ultraviolet radiation (UVR; 280–400 nm). These irradiance fluctuations are now superimposed upon ocean acidification and thinning of the upper mixing layer through stratification, which alters mixing regimes. Therefore, we examined the photosynthetic carbon fixation and photochemical performance of a coccolithophore, Gephyrocapsa oceanica, grown under high, future (1,000 μatm) and low, current (390 μatm) CO2 levels, under regimes of fluctuating irradiances with or without UVR. Under both CO2 levels, fluctuating irradiances, as compared with constant irradiance, led to lower nonphotochemical quenching and less UVR-induced inhibition of carbon fixation and photosystem II electron transport. The cells grown under high CO2 showed a lower photosynthetic carbon fixation rate but lower nonphotochemical quenching and less ultraviolet B (280–315 nm)-induced inhibition. Ultraviolet A (315–400 nm) led to less enhancement of the photosynthetic carbon fixation in the high-CO2-grown cells under fluctuating irradiance. Our data suggest that ocean acidification and fast mixing or fluctuation of solar radiation will act synergistically to lower carbon fixation by G. oceanica, although ocean acidification may decrease ultraviolet B-related photochemical inhibition. Fil: Jin, Peng. Xiamen University. State Key Laboratory of Marine Environmental Science; China Fil: Gao, Kunshan. Xiamen University. State Key Laboratory of Marine Environmental Science; China Fil: Villafañe, Virginia Estela. Fundación Playa Unión. Estación de Fotobiología Playa Unión; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Campbell, Douglas A. Mount Allison University. Biology Department; Canadá Fil: Helbling, Eduardo Walter. Fundación Playa Unión. Estación de Fotobiología Playa Unión; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional ...